2022
DOI: 10.1155/2022/7587398
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Understanding the Critical Role of Glycolysis‐Related lncRNAs in Lung Adenocarcinoma Based on Three Molecular Subtypes

Abstract: Background. Glycolysis is closely associated with tumor progression, but the roles of lncRNAs in glycolysis have not been comprehensively investigated in lung adenocarcinoma (LUAD). This study is aimed at studying the possible mechanisms of glycolysis-related lncRNAs in tumor development and providing a guidance for targeted therapy. Methods. Unsupervised consensus clustering was used to identify molecular subtypes. Gene enrichment analysis was applied to screen important pathways involved in tumor progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…LncRNA FAM83A-AS1 contributed to cell proliferation and stemness via the HIF-1α/glycolysis axis [24]. Cao et al identi ed four critical glycolysis-related LncRNAs associated with prognosis [25]. Therefore, searching for new LncRNAs in LUAD targeting glycolysis is of great signi cance.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA FAM83A-AS1 contributed to cell proliferation and stemness via the HIF-1α/glycolysis axis [24]. Cao et al identi ed four critical glycolysis-related LncRNAs associated with prognosis [25]. Therefore, searching for new LncRNAs in LUAD targeting glycolysis is of great signi cance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FTX, LINC00472, PSMA3-AS1, and SNHG14 are the 4 critical glycolysis-related lncRNAs [ 62 ]. Through the regulation of 22/FOXM1 axis, lncRNA NNT-AS1 plays a key role in carcinogenesis in NSCLC, thus a novel pathogenesis and a paradigm shift into the therapeutic target for these forms of cancer [ 63 ]. The immunotherapy of LUSC is influenced by tumor-infiltrating immune cells (TIICs), pathological stage, metabolism, and also the survival of patients [ 64 ].…”
Section: Inhibiting the Synthesis Of Biomoleculementioning
confidence: 99%
“…Recent progress in systems biology has shown that several specific factors are participants of a network that function as master regulators of cancer [1][2][3]. Wilson and Volker Filipp investigated complementary omics in human cancer, and discovered a close teamwork of transcriptional and epigenomic machinery, which is tightly connected and comprises histone lysine demethylase 3A, basic helix-loop-helix factors, MYC, hypoxiainducible factor 1 alpha (HIF1A), and sterol regulatory element-binding transcription factor 1, as well as differentiation factors such as activator protein 1, myogenic differentiation 1, specificity protein 1 (SP1), Meis homeobox 1, zinc finger E-box-binding homeobox 1, and ETS like-1 protein (ETS1) [1].…”
Section: Introduction: Specificity Protein 1 Hypoxia-inducible Factor...mentioning
confidence: 99%